Experimental investigation on creep behaviour of composite sandwich panels constructed from polystyrene/cement-mixed cores and thin cement sheet facings. Issue 1 (2nd January 2019) - Far, Harry; Far, Claire
ABSTRACT: Composite sandwich panels have gradually become more popular due to their typical benefits including strength, weight, ease of handling, durability, versatility, thermal and acoustic properties. Many researchers are aware of these benefits and have undertaken detailed research and publicised large amounts of scientific papers on composite sandwich panels. With the variety of loads that could possibly be applied to a structure, often the in-service life behaviour is significant. Reviewing whether it will function correctly and without excessive deformations is a factor that can sometimes impact the performance. Polystyrene/Cement-mixed cores and thin cement sheet facings composite sandwich panels are Australian products made of cement–polystyrene beaded mixture encapsulated between two thick cement board sheets. The creep and creep recovery properties of these sandwich panels are relatively unknown. Therefore, in this study, in order to understand the creep and creep recovery behaviour of those sandwich panels, a series of experimental tests have been performed and the outcomes have been explained and discussed. Based on the results of this study, values for immediate recovery, creep recovery and irrecoverable creep strain are determined and proposed. In addition, typical creep and creep recovery design curves have been developed and presented for practical applications in structural engineering.